2012
DOI: 10.1080/00207594.2012.658055
|View full text |Cite
|
Sign up to set email alerts
|

Risk and resilience: The moderating role of social coping for maternal mental health in a setting of political conflict

Abstract: Violence can threaten individual well-being and tear at the social fabric of communities. At the same time, suffering can mobilize social coping and mutual support. Thus, the backdrop of political violence increases risk factors and stimulates resilience. The current study examined the moderating role of social coping as reflective of risk and resiliency in Northern Ireland, a setting of protracted conflict. Specifically, structural equation modeling was used to investigate whether social coping protects from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Social identity as reflected in ethnic group identity has long been held pertinent to understanding the impact of contexts of intergroup sectarian conflict (Cairns, 1996). Social identity refers to an individual's self-categorization as a member of a particular group and the evaluative meaning of that group membership (Tajfel & Turner, 1979). Thus, the strength of identification with a group in conflict is likely to alter the psychological experience of group-based conflicts such as that in Northern Ireland.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…Social identity as reflected in ethnic group identity has long been held pertinent to understanding the impact of contexts of intergroup sectarian conflict (Cairns, 1996). Social identity refers to an individual's self-categorization as a member of a particular group and the evaluative meaning of that group membership (Tajfel & Turner, 1979). Thus, the strength of identification with a group in conflict is likely to alter the psychological experience of group-based conflicts such as that in Northern Ireland.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…Following the peace agreements in South Africa and Northern Ireland, levels of common crime have increased as forms of political or sectarian violence declined (Police Service of Northern Ireland, ; Shirlow et al., ; van der Merwe & Dawes, ). The impact of non‐sectarian crime, or intra‐group antisocial behaviors, has also been shown to have distinct effects on child adjustment and family processes (Cummings et al., , ; Taylor et al., ). Other post‐accord challenges, such as daily hardships and community acceptance, have also been found to have predictive power for youth outcomes independent of war experiences (Betancourt et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al (2012) found that social support protected mental health from the negative effects of nonsectarian violence, but exacerbated mental health problems resulting from sectarian (i.e. political) violence.…”
Section: Opportunities For Social Supportmentioning
confidence: 99%